2004
DOI: 10.1002/cvde.200306284
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Tris(β‐ketoiminato)ruthenium(III) Complexes: Potential Precursors for CVD of Ru and RuO2 Thin Films

Abstract: The synthesis and characterization of Ru III metal complexes [Ru(keim1) 3 ] (1) and [Ru(keim2) 3 ] (2) are reported, where (keim)H is an abbreviation for the fluorinated ketoimine ligands with formula HOC(CF 3 )=CHCR=NMe; (keim1)H with R = Me and (keim2)H with R = CF 3 . These newly synthesized complexes were characterized by spectroscopic methods, while the second complex, 2, was further examined by single-crystal X-ray diffraction (XRD), revealing an octahedral coordination for the Ru cation, with three keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…The resulting metal complexes could be promising candidates which potentially fulfill the criteria of volatility, suitable reactivity and sufficient thermal stability ( Scheme ) for atomic layer deposition and sufficient temperature window between volatilization and decomposition for low‐temperature CVD applications. Metal ketoiminates have been considered and applied as precursors for the CVD of metal oxides and nitrides of various transition metals, e.g., Ru, Ta, Nb, Zn, Pd, Cu, Ni, Ir, Ti . So far, none of these compounds have been tested for ALD applications, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting metal complexes could be promising candidates which potentially fulfill the criteria of volatility, suitable reactivity and sufficient thermal stability ( Scheme ) for atomic layer deposition and sufficient temperature window between volatilization and decomposition for low‐temperature CVD applications. Metal ketoiminates have been considered and applied as precursors for the CVD of metal oxides and nitrides of various transition metals, e.g., Ru, Ta, Nb, Zn, Pd, Cu, Ni, Ir, Ti . So far, none of these compounds have been tested for ALD applications, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of ligand 3 described below. The five ruthenium complexes of the corresponding ligands were synthesized by using literature methods of related complexes as a guide [19,12].…”
Section: Synthesismentioning
confidence: 99%
“…x / RuCl3 . 3H2O) with the corresponding ketoimine ligands [12], or by stirring a mixture of RuCl3 . 3H2O and the relevant ketoimine ligand at room temperature [19].…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…This can also account for the greater stability of the source precursor. 78 Under inert gas ow the mass loss of the precursor out of a crucible with time is nearly linear (for the exact theory, see ref. 81) and the residual mass should be negligible.…”
Section: Desirable Properties Of Cvd Precursorsmentioning
confidence: 99%
“…Chou et al 78 synthesized two octahedral Ru(III) complexes such as [Ru(keim1) 3 ] 49 and [Ru(keim2) 3 ] 50, (keim1 ¼ -OC(CF 3 ) ¼ CHC-CH 3 ¼ NMe, keim2 ¼ -OC(CF 3 ) ¼ CHC-CF 3 ¼ NMe) with good volatility and thermal stability. The CVD study showed that the lm structures varied according to the nature of source reagent and carrier gas.…”
Section: (B) Organometallic Ruthenium Derivativesmentioning
confidence: 99%